Penerapan Model AHP Pada Pemilihan Aplikasi Streaming Drama Korea - Fajar Agustini; Khoirun Nisa (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2021)
Technology is developing very fast and is increasingly global, various kinds of the latest technological discoveries and various kinds of applications offered by each company will continue to compete, one of which is the Korean drama streaming application program. However, it is not just one Korean drama streaming application, but many other streaming applications that have sprung up and can make users hesitate to choose a streaming application to watch quality Korean dramas. Selection of useful criteria for selecting Korean drama streaming applications using the Analytical Hierarchy Process approach and processing using Expert Choice software allows streaming application users to know how to choose a streaming application to watch Korean dramas as desired. The population of this study were several Bekasi city people with approximately 30 questionnaires. From the research results, it was found that VIU was a strategic alternative for selecting Korean drama streaming applications using the Analytical Hierarchy Process which received top priority with a weight of 0.499 or comparable to 49.9% of another alternative. Keywords: Streaming application, Korean Drama, Analytical Hierarchy Process